Kajian Hukum Terhadap Pelaku Tindak Pidana Kebakaran Hutan di Kawasan Hutan Provinsi Sumatera Utara (Di Dusun II Desa Sarimarihit Kecamatan Sianjur Mula-Mula Kabupaten Samosir) - Putri Ivana Martsaulina Gok Asi Tampubolon; Immanuel Simanjuntak (Jurnal Hukum Lex Generalis, 2025)
A forest is a land or large land that stretches where there are many green trees, forests are also a habitat for wildlife and other living creatures such as animals, plants or other organisms. If you look at the many forest fires in Indonesia, in particular, forests in the North Sumatra region have also been found to have many forest fires. One example of forest fires that occurred in the Samosir Regency area is that in this case there has been a forest fire covering an area of ±22.9 ha. This research was carried out to find out how criminal responsibility for perpetrators of forest crimes in the forest area of North Sumatra Province, (in Hamlet II, Sarimarihit Village, Sianjur Mula-Mula District, Samosir Regency) as well as to find out how the judge considers the perpetrators of forest fires in the forest area of North Sumatra Province (in Hamlet II, Sarimarihit Village, Sianjur Mula-Mula District, Samosir Regency). The type of research used is normative juridical in nature, which focuses on laws and court decisions. The crime of forest fire committed by the perpetrator has been proven and meets the elements so that in this case the perpetrator is charged with a criminal sentence of 1 year and a fine of 500 million rupiah and the judge's consideration of the perpetrator has been objectively applied and by considering the existing evidence. Until in this case, with the crime of forest fire committed by the perpetrator, he should be sentenced to prison with the maximum penalty.